Cissococcus Cockerell (Hemiptera: Coccoidea: Coccidae), a unique gall-inducing soft scale genus on Vitaceae from South Africa, with description of a new species - Hodgson, C. J.; Millar, I. M.; Gullan, P. J. (Zootaxa, 2011)
The gall-inducing genus Cissococcus Cockerell is revised to include two species. The family placement of Cissococcus has been uncertain, but characters of the first-instar nymph and adult male clearly show that Cissococcus is a soft scale insect (Coccidae) and is therefore the only member of the Coccidae known to induce a complex covering gall. All stages of the type species, C. fulleri Cockerell, are described and illustrated, plus the adult and third-instar female and first-instar nymph of a new, closely-related species, C. braini Hodgson & Millar sp. n. Both species are known only from wild vines in the southeast and C. fulleri also in the northeast of South Africa, but each induces a unique gall and each appears to be restricted to a different species of Rhoicissus (Vitaceae). The galls of each species are described and figured, and gall induction in the Coccidae is briefly discussed.